Springtime connections between the large-scale sea-level pressure field and gust wind speed over Iberia and the Balearics - M. L. Martín; F. Valero; A. Pascual; A. Morata; M. Y. Luna (Natural Hazards and Earth System Sciences, 2011)
This paper investigates, by means of Singular Value Decomposition analysis, the springtime relationships between the mean sea-level pressure field over the North Atlantic and the regional wind gusts over the Iberian Peninsula, identifying the main atmospheric circulation patterns linked to gust wind speed anomaly configurations. The statistical significance of the obtained modes is investigated by means of Monte Carlo approach. The analysis highlighted that the covariability is dominated by two main large-scale features of the atmospheric circulation over the North Atlantic. The first mode relates to Iberian gust wind speeds to the Scandinavian pattern (SCAND), linking the large-scale pattern to above-normal wind gusts. The second covariability mode, associated with the North Atlantic Oscillation (NAO) pattern, correlates with maximum wind speeds over Iberia. An enhanced spring NAO pattern is related to positive (negative) wind gust correlations over northern (southern) Iberia. To find true relationships between large-scale atmospheric field and the gust wind speeds, composite maps were built up to give an average atmospheric circulation associated with coherent wind gust variability over Iberia.